Swish! : the slam-dunking, alley-ooping, high-flying Harlem Globetrotters - Slade, Suzanne (Little, Brown and Company, 2020)
"In this book you will find one-finger ball-spinning, rapid-fire mini-dribbling, and a ricochet head shot!You will find skilled athletes, expert players, and electrifying performers, all rolled into one! You will find nonstop, give-it-all-you've-got, out-to-win-it, sky's-the-limit BASKETBALL!